The effectiveness of adaptive learning media based on realistic mathematics education on cube and block materials in Madrasah Ibtidaiyah - Syaripudin, Ahmad; Sulistyowati, Endang; Narfi, Muhammad Afif; Bintang, Rahma Sahanum (Universitas Islam Negeri Raden Intan Lampung, 2026)
The low conceptual understanding of elementary school students towards geometry, especially cube and block materials, remains a challenge for learning basic mathematics. This condition is exacerbated by predominantly conventional learning practices, a lack of context, and a lack of responsiveness to the diversity of student characteristics, including in inclusive classes. This study aims to develop and evaluate the effectiveness of adaptive learning media grounded in (RME) in improving students’ mathematics learning outcomes. The research used a Research and Development (R and D) approach, employing the ADDIE model, combined with a quasi-experimental design with a non-peer control group. The study involved grade V students of Madrasah Ibtidaiyah (MI) in rural and urban areas, including students with disabilities. Data were collected through learning outcome tests and analyzed using descriptive and inferential statistics (t-tests). The results of the study show that RME-based adaptive learning media are declared valid and practical, and significantly more effective than conventional learning. These findings suggest that integrating adaptive media can strengthen the implementation of RME and support contextual, inclusive, and evidence-based geometry learning.